1, 6-Naphthodipyrrolidone-based donor–acceptor polymers with low bandgap. (9th March 2015) - Zhang, Haichang; Ying, Shian; Tieke, Bernd; Zhang, Jun; Yang, Wenjun
Abstract: Donor–acceptor (D–A) copolymersP1 –P4 containing 1, 6-naphthodipyrrolidone as acceptor unit are synthesized and characterized. CopolymersP1 andP2 are prepared upon Suzuki coupling of 3, 8-di(4-bromophenyl)-1.6-bis(dodecyl)-2, 7-dioxo-1, 2, 6, 7-tetrahydronaphtho[1, 2- b :5, 6- b ′]dipyrrole (M1 ) or 3, 8-di-(4-bromophenyl)-1.6-bis(2-octyldodecyl)-2, 7-dioxo-1, 2, 6, 7-tetrahydronaphtho[1, 2- b :5, 6- b ′]dipyrrole (M2 ) with the donor comonomer 2, 2-(9, 9-dioctyl-9H-fluoren-2, 7-diyl)-bis-(4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolane) (M3 ). PolymersP3 andP4 are prepared upon Stille coupling ofM1 orM2 with the donor comonomer 4, 8-bis(2-ethylhexyloxy)benzo[1, 2- b :4, 5- b ]dithiophene-2, 6-diyl-bistrimethylstannaneM4 . The two monomersM1 andM2 exhibit a deep purple color in dichloromethane with high extinction coefficients up to 4.9*10 4 L mol −1 cm −1 . Optical, electrochemical and thermal properties of the polymers are characterized. The polymers exhibit a broad UV/vis absorption range from 400 to 850 nm, low optical bandgaps (1.27–1.47 eV), low LUMO levels (especially forP1 andP2 ), a high thermal stability with glass temperature T g up to 224 ° C, and 5% weight loss up to 402 ° C. Density functional theory calculations indicate that the backbone of the 1, 6-NDP-polymers is rather planar. Photostability studies indicate a high stability against UV-irradiation in the solid state, but only a moderate stability upon UV irradiation in solution. Graphical abstract: Highlights: Four novel donor–acceptor copolymersP1 –P4 containing the naphthodipyrrolidone unit in the main chain have been synthesized. The polymers exhibit good thermal stability and photostability in the solid state. The polymers exhibit a broad UV/vis absorption in the visible ranging from 400 to 850 nm with high extinction coefficients. The bandgaps of the polymers are low.